Career Adaptability of Marine Cadets: A Descriptive Study - Wiwik Sulistiani; Dewi Retno Suminar; Wiwin Hendriani (Journal of Educational, Health and Community Psychology, 2019)
Issues pertaining to career often arise during higher education period. Common problems during such period of career development include choosing, deciding, and maintaining a career, including maintaining oneâ€™s choice of career. The aim of this study is to describe the career adaptability of shipping cadets. Participants are shipping cadets from a private university in Surabaya, Indonesia. Data was collected using an Indonesian version of Career Adaptability scale (CAAS). Result provides description on cadetsâ€™ career adaptability, as follows: 8% was categorized as â€œlowâ€, 23.2% â€œmoderateâ€, and 76% â€œhighâ€. Comparison of standard deviations shows that the career adaptability of shipping cadets had low variation. Percentages of each indicator are as follows: the indicator of â€œconcernâ€ ranked first (26.41%), â€œcontrolâ€ at second (25.85%), â€œconfidenceâ€ at third (24.24%), and â€œcuriosityâ€ at fourth (23.47%). It shows that all indicators of career adaptability among shipping cadets played roles in shaping career adaptability and have balanced similarities.